Balancing contradictory temporality during the unfold of innovation streams. Issue 6 (August 2016) - Simon, Fanny; Tellier, Albéric
Abstract: This article focuses on individuals working on innovation developments during the unfolding of innovation streams. Innovation streams include both exploitation- and exploration-oriented projects. Those projects imply different temporalities and can be conducted at different paces. This research examines how different temporalities within a single innovation stream are managed first at the level of projects and then among projects. We collected data on an innovation stream in the semiconductor industry. We explain how teams and organization develop processes and tools to address different temporalities. The results show that the process of learning occurs first within projects and then among projects. Our research offers new understandings of the transition of organizations towards a project-based structure by demonstrating that changes in practices can occur first as a reaction to external events, then as the results of new arrangements triggered by management and finally as the consequences of the team's proactive actions. Highlights: Innovation streams include both exploitation- and exploration-oriented projects. Projects imply different temporalities and can be conducted at different paces. We examine how actors move from project to project that have different temporalities. We demonstrate that time pacing is learnt by teams as they move from exploration to exploitation.